President’s Message - Socha, Linda (Operating Room Nurses Association of Canada Journal, 2009)
It’s hard to imagine that the first quarter of 2009 is already over! As my term as President is nearing its end, I am feeling a bit nostalgic. I remember my very first ORNAC national conference in Halifax in 1999. Immediately after that conference, I got involved with ORNAC. With some encouragement and gentle persuasion, as well as a great deal of support from a mentor, I ran for office in my provincial operating room nurses group. One thing led to another and flash forward 10 years… here I am writing to you as President of ORNAC. The fact that St. John’s, NL, will be the host city for our 21st National Conference, in June of this year, makes my experience as President even more special. My ORNAC experience will have come full circle as it began, and will conclude, in Atlantic Canada!